Michael Haneke : Interviews - Root, Colin; Naqvi, Fatima; Grundmann, Roy, 1963- (Book collections on Project MUSE., 2020)
Spanning five decades and twenty-four films, director Michael Haneke's career is one of the most significant in the history of European art cinema. However, critical reception has long lagged behind his output. By the time Haneke (b. 1942) emerged into the international spotlight as a cinematic visionary with the 1989 Cannes premiere of The Seventh Continent, he had worked in filmmaking for two decades, producing seven feature-length films. As many of his films aired solely on Austrian and German television, they remained unknown to audiences outside the German-speaking world until 2007, when the first comprehensive Haneke retrospective took place in the United States. Michael Haneke: Interviews presents some of Haneke's most profound interviews to English speakers. The volume features seventeen articles, fourteen of which have been translated into English for the first time, and all of which provide a detailed, eloquent commentary on his films and worldview. This book represents the most extensive collection to date of interviews with the filmmaker, spanning his entire oeuvre--from his earliest television films to his so-called "Glaciation Trilogy" of the 1990s, from the notorious dark satire Funny Games to its similarly notorious 2007 Hollywood remake, and from his French films of the 2000s to his Oscar-winning drama, Amour, and his most recent feature, Happy End.--Provided by publisher.